Population forecasting with the Box-Jenkins approach - Peter Pflaumer (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1991)
The use of the Box-Jenkins approach for forecasting the population of the United States to the year 2080 is discussed. The forecasts are based on data for 1900-1980. It is shown that no major difference exists between the Box-Jenkins approach and parabolic trend curves when making long-range predictions. An investigation of forecasting accuracy indicates that the Box-Jenkins method produces population forecasts that are at least as reliable as those done with more traditional demographic methods.
Keywords: 330; Zeitreihenanalyse; Bevölkerungsprognose; USA